(untitled) (Journal of Informatics and Mathematical Sciences, 2024)
We have introduced characterized semiring in this study. We have discussed the properties of ideals in semiring and characterization of semirings using ideals and some applications. We have also talked of bi-ideal and quasi-ideal in semiring and its significant classes. We have characterized three significant classes namely regular semiring, intra-regular semiring and weakly regular semiring using quasi ideals and bi-ideals.